TOXICITY AND ANTI-INFLAMMATORY EFFECTS OF METHANOLIC EXTRACT OF UMBILICUS RUPESTRIS L. LEAVES (CRASSULACEAE) - AFAFBENHOUDA,; MOULOUD YAHIA, (International Journal of Pharma and Bio Sciences, 2015)
Umbilicus rupestris (UR) is a medicinal plant used in traditional medicine against inflammation and irritation of the skin. The aim of this work is to study in vivo on Wistar rats the acute and subacute toxicity of the methanolic extract of U. rupestris (URMeOH ), anti -inflammatory effects by using several methods : The inflammation induced by carrageenan, the inflammation induced by the inflammation mediators, arthritis , peritonitis in Wistar rats and finally, effect of URMeOH on the stabilization of erythrocyte membrane in vitro . In the acute toxicity study, the LD50 of URMeOH was found higher than 2000 mg / kg b.w ; and this dose did not cause neither death nor signs of toxic manifestations on treated rats . In the subacute toxicity study , no toxic signs were observed after 28 days of treatment with therapeutic doses 100 and 200 mg / kg b.w. The inflammation induced by carrageenan, chemical mediators (histamine and serotonin) and formalin solution was significantly inhibited and dose-dependent manner compared to the negative control after the administration of URMeOH (100 mg and 200 mg / kg B.w.). Also, the URMeOH revealed that it has an effect on the stabilisation of erythrocyte membrane after induction of hemolysis and it has the anti-peritonitis activity by inhibiting leukocytes migration.This study demonstrated the anti -inflammatory effects of URMeOH and that confirmed its use in traditional medicine.